2018
DOI: 10.1111/jan.13799
|View full text |Cite
|
Sign up to set email alerts
|

Social media in nursing and midwifery education: A mixed study systematic review

Abstract: This review provides the first rigorous synthesis of social media in nursing and midwifery education. A new Social Media Learning Model was conceptualized to aid our understanding of learning via this technology. Knowledge gaps are identified and recommendations on how to capitalize on social media to improve learning in higher and continuing education provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 47 publications
0
34
1
1
Order By: Relevance
“…Here are presented some of the most comprehensive ones available to the authors. The first one deals with the social media as advanced electronic tools used to support learning among nursing and midwifery students (O'Connor et al, 2018). The key findings of this study are that social media can aid acquiring knowledge and skills among nursery and midwifery students, enhancing confidence, and facilitating professional and personal networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Here are presented some of the most comprehensive ones available to the authors. The first one deals with the social media as advanced electronic tools used to support learning among nursing and midwifery students (O'Connor et al, 2018). The key findings of this study are that social media can aid acquiring knowledge and skills among nursery and midwifery students, enhancing confidence, and facilitating professional and personal networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the effect of social media in education was deemed mixed at best, with the quality of studies considered as modest. A systematic review of social media in nursing and midwifery education (O'Connor et al, 2018) highlighted benefits of implementing social media in nursing curricula. For example, allowing information to be shared in real-time, supporting a student-centred learning setting and enhancing collaborative learning.…”
Section: Social Mediamentioning
confidence: 99%
“…Rather than seeing social media as a potential pitfall it has been suggested that it could be reimagined as professional media. A systematic review of the use of social media in nursing and midwifery education found that the interactive nature of social media can support student learning, facilitate professional networks, and increase confidence (O'Connor et al 2018). By increasing confidence with regard to social media from a professional perspective, opportunity for professional development is increased, for example, the use of Twitter as an interactive tool across professional groups (Bliss 2016).…”
Section: Professional Practice Guidelinesmentioning
confidence: 99%